2018
DOI: 10.1016/s1473-3099(18)30132-4
|View full text |Cite
|
Sign up to set email alerts
|

EUSeqMyTB to set standards and build capacity for whole genome sequencing for tuberculosis in the EU

Abstract: 2 ECDC, WHO Regional Office for Europe. Tuberculosis surveillance and monitoring in Europe 2018-2016 data. Stockholm: European Centre for Disease prevention and Control (ECDC), 2018. 3 Kendall EA, Fofana MO, Dowdy DW. Burden of transmitted multidrug resistance in epidemics of tuberculosis: a transmission modelling analysis. Lancet Respir Med 2015; 3: 963-72. 4 Walker TM, Kohl TA, Omar SV, et al. Whole-genome sequencing for prediction of Mycobacterium tuberculosis drug susceptibility and resistance: a retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 4 publications
0
27
0
Order By: Relevance
“…Using this dataset, the EUSeqMyTB consortium showed that existing pipelines could confidently distinguish linked from unlinked cases, especially when the SNP distances are high, as is often the case in low burden settings 12 . This comparison was 259 undertaken as part of an effort to standardise WGS for monitoring MDR-TB cross border 260 transmission in Europe 15 .…”
Section: Validation Of Transmission Clusteringmentioning
confidence: 99%
See 3 more Smart Citations
“…Using this dataset, the EUSeqMyTB consortium showed that existing pipelines could confidently distinguish linked from unlinked cases, especially when the SNP distances are high, as is often the case in low burden settings 12 . This comparison was 259 undertaken as part of an effort to standardise WGS for monitoring MDR-TB cross border 260 transmission in Europe 15 .…”
Section: Validation Of Transmission Clusteringmentioning
confidence: 99%
“…. Rapid, reliable, and increasingly affordable 105 WGS technologies, can now guide all components of TB control: diagnosis, treatment, 106 surveillance and contact tracing 5,6 (Fig. 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Several large-scale projects are ongoing to set guidelines/standards and ensure better (inter)national integration of WGS-based systems [ 10 ]. The obvious obstacle of the implementation in low resource, high-incidence settings is also being tackled e.g.…”
mentioning
confidence: 99%